2020
DOI: 10.1038/s41598-020-73274-y
|View full text |Cite
|
Sign up to set email alerts
|

Integrated transcriptomic and metabolomic data reveal the flavonoid biosynthesis metabolic pathway in Perilla frutescens (L.) leaves

Abstract: Perilla frutescens (L.) is an important medicinal and edible plant in China with nutritional and medical uses. The extract from leaves of Perilla frutescens contains flavonoids and volatile oils, which are mainly used in traditional Chinese medicine. In this study, we analyzed the transcriptomic and metabolomic data of the leaves of two Perilla frutescens varieties: JIZI 1 and JIZI 2. A total of 9277 differentially expressed genes and 223 flavonoid metabolites were identified in these varieties. Chrysoeriol, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
29
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 52 publications
4
29
4
Order By: Relevance
“…Subsequently, 4-Coumaric-CoA is converted to naringenin catalyzed by CHS and CHI. While naringenin is the key metabolite in flavonoid synthesis (Figure 6), catalyzed by different enzymes, the naringenin produces three branches, one branch produces flavonoid (eriodictyol, apigenin, and luteolin), the second branch produces flavonols (dihydrokaempferol, kaempferol, dihydroquercetin, and quercetin), and the third branch produces isoflavones, which is in agreement with the previous findings (Gao et al, 2020;Jiang et al, 2020). here have been reports that naringenin possesses a broad range of biological activities, such as anti-oxidant, hepatoprotective, anti-inflammatory, and anticarcinogenic effects (Raso et al, 2001), and the pharmacological potential of flavonoids in D. huoshanense needs to be further explored.…”
Section: Discussionsupporting
confidence: 92%
“…Subsequently, 4-Coumaric-CoA is converted to naringenin catalyzed by CHS and CHI. While naringenin is the key metabolite in flavonoid synthesis (Figure 6), catalyzed by different enzymes, the naringenin produces three branches, one branch produces flavonoid (eriodictyol, apigenin, and luteolin), the second branch produces flavonols (dihydrokaempferol, kaempferol, dihydroquercetin, and quercetin), and the third branch produces isoflavones, which is in agreement with the previous findings (Gao et al, 2020;Jiang et al, 2020). here have been reports that naringenin possesses a broad range of biological activities, such as anti-oxidant, hepatoprotective, anti-inflammatory, and anticarcinogenic effects (Raso et al, 2001), and the pharmacological potential of flavonoids in D. huoshanense needs to be further explored.…”
Section: Discussionsupporting
confidence: 92%
“…These results suggest that AM symbiosis may improve the biosynthesis of flavonols and flavanols and suppress the accumulation of anthocyanidins. Furthermore, TF-encoding gene analysis showed that the transcription factor families involved in flavonoid biosynthesis, including the MYB, bHLH, and NAC families 44 46 , were responsive to mycorrhizal symbiosis, and most TFs of these three families were upregulated in the AMF treatment group. Taken together, the biosynthesis of flavonoids was strongly affected by AMF colonization, which may be the most direct factor underlying the enhancement of resistance to gypsy moth larvae in P. alba × P. berolinensis seedlings under the AM fungus treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The phenylpropanoid biosynthetic pathway is activated under stress conditions, resulting in accumulation of various phenolic compounds which, among other roles, have the potential to scavenge harmful reactive oxygen species (ROS) [ 24 , 25 , 26 ]. In recent years, metabolomics integrated with transcriptomics has been widely used to investigate the biosynthesis of metabolites in plants [ 27 , 28 ]. In this study, hydrogen water was used to treat the famous Chinese southern medicine Wuzhimaotao, and then the metabolome and transcriptome were analyzed.…”
Section: Discussionmentioning
confidence: 99%